Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 434: 120



Work Step by Step

$\sqrt[3] (a^{9}b^{21}c^{3})=\sqrt[3] (a^{9}\times b^{21}\times c^{3})=\sqrt[3] (a^{9})\times \sqrt[3] (b^{21})\times \sqrt[3] (c^{3})=a^{3}b^{7}c$ $\sqrt[3] (a^{9})=a^{3}$, because $(a^{3})^{3}=a^{3\times3}=a^{9}$ $\sqrt[3] (b^{21})=b^{7}$, because $(b^{7})^{3}=b^{7\times3}=b^{21}$ $\sqrt[3] (c^{3})=c$, because $(c)^{3}=c^{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.